(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
This project presents a Hybrid Solar and Kinetic Energy Harvesting System designed for efficient energy harvesting and smart microgrid management. The system integrates a 12V battery, charged via a photovoltaic (PV) cell and an energy harvesting mechanism from a speed breaker, ensuring a sustainable power supply. One 1W solar panel, each monitored by a voltage sensor, provide real-time voltage data to an Arduino UNO microcontroller. Simultaneously, the speed breaker-based energy harvester contributes additional power, monitored through a voltage sensor. To enhance system intelligence and remote accessibility, an IoT-enabled Wi-Fi module transmits real-time power data to an online monitoring platform. The system optimizes power distribution across three load stations using relay-based control, allowing dynamic load management based on power availability and demand. By integrating solar and kinetic energy sources, this project enhances energy efficiency and reliability in smart microgrid applications.